Tetrazoles: calcium oxalate crystal growth modifiers - McMulkin, Calum; Massi, Massimiliano; Jones, Franca (The Royal Society of Chemistry, 2015)
Molecules containing tetrazole substituents have become of interest due to their being bioisosteres of carboxylic acids and like their carboxylate counterparts, tetrazolate anions have been able to affect the crystal growth of barium sulphate and calcium carbonate. In this proof of principle study, we show that this behaviour also extends to calcium oxalate and therefore opens the possibility of using tetrazole-based additives for investigating mineralization processes of human pathological relevance.